Comparison of Treatment Outcome of Ganciclovir Ophthalmic Gel and Moxifloxacin Eye Drop in Acute Adenoviral Keratoconjunctivitis (Mugda Medical College Journal, 2024)
Adenoviral ophthalmic infection is a self-limiting, highly contagious, very frequent infectious process. It can present in three acute clinical forms: nonspecific acute follicular conjunctivitis, pharyngo-conjunctival fever and epidemic keratoconjunctivitis. This study aims to assess and compare the efficacy of 0.15% ganciclovir gel with Moxifloxacin eye drop in the treatment of acute adenoviral keratoconjunctivitis.This longitudinal prospective study was conducted among 40 patients of acute adenoviral keratoconjuctivitis attending in the cornea clinic of National Institute of Ophthalmology & Hospital (NIOH), Dhaka, Bangladesh. They were randomly divided into two groups: group-I (study group) with 20 patients who used 0.15% ganciclovir gel and group-ii (control group) with 20 patients who used artificial tear and 0.5% moxifloxacin eye drop. Diagnosis was confirmed by expert cornea specialist by methodical ophthalmic examination. They were followed-up on 1,2,4 and 6 weekly. Mean score of symptoms and signs were calculated in every follow-up and compared between two groups. Unpaired t test and chi square test were done in applicable cases with statistical significance p